Spiritual-Integrated Interpersonal Communication in Mentoring Children with Special Needs - Belekubun, Susilawati; Renwarin, Martinus; Talubun, Michael; Futauni, Maria Irmawati (Jurnal Komunikasi Pemberdayaan, 2025)
This study examines interpersonal communication practices in mentoring children with special needs conducted by the ALMA Sisters at Bhakti Luhur Orphanage in Langgur, Southeast Maluku. Children with special needs often experience communication barriers, limited social interaction, and social stigma within their communities. Effective interpersonal communication therefore becomes a crucial element in the mentoring process. This research employs a qualitative approach using a case study design. Data were collected through in‑depth interviews, participant observation, and document analysis involving sisters who directly assist children with special needs. The data were analyzed thematically to identify patterns of interpersonal communication that emerge in the mentoring process. The findings reveal six dominant forms of interpersonal communication in mentoring practices: openness, empathy, supportiveness, equality, contextual awareness, and sacrifice. These communication practices function not only as interaction mechanisms but also as relational strategies that foster emotional security, self‑confidence, and social development among the children. Furthermore, the religious spirituality embraced by the sisters strengthens the interpersonal relationships established during the mentoring process.This study contributes to interpersonal communication scholarship by highlighting the integration of spiritual values within mentoring practices for children with special needs.